2014
DOI: 10.1021/cb5007689
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Trehalose Mycolates Is Required for Efficient MmpL-Mediated Membrane Transport in Corynebacterineae

Abstract: Pathogenic species of Mycobacteria and Corynebacteria, including Mycobacterium tuberculosis and Corynebacterium diphtheriae, synthesize complex cell walls that are rich in very long-chain mycolic acids. These fatty acids are synthesized on the inner leaflet of the cell membrane and are subsequently transported to the periplasmic space as trehalose monomycolates (TMM), where they are conjugated to other cell wall components and to TMM to form trehalose dimycolates (TDM). Mycobacterial TMM, and the equivalent Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(97 citation statements)
references
References 42 publications
6
90
1
Order By: Relevance
“…42 TMM acetylation would follow the transfer of mycolic acids onto trehalose by Pks13 43 and, perhaps, serve as a signal for export by MmpL3 or another component of the mycolic acid translocation machinery. Whether acetylation is required for TMM export in mycobacteria was not known.…”
Section: Resultsmentioning
confidence: 99%
“…42 TMM acetylation would follow the transfer of mycolic acids onto trehalose by Pks13 43 and, perhaps, serve as a signal for export by MmpL3 or another component of the mycolic acid translocation machinery. Whether acetylation is required for TMM export in mycobacteria was not known.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that the C. glutamicum acetyltransferase TmaT (TMCM mycolyl acetyltransferase; NCgl2759) catalyzes the acetylation of the major cell wall glycolipid TMCM and that this modification is important for periplasmic transport of this glycolipid (41). A subsequent study showed that the mycobacterial orthologue has the same function (44).…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid sequence alignments were produced using Clustal Omega. Construction of C. glutamicum ⌬NCgl2760 and Complementation Strains-The NCgl2760 gene was deleted using a twostep allelic replacement strategy previously used in our laboratory to create other cell wall mutants (11,16,29,41). A 1.0-kb fragment containing sequence from the left side of the NCgl2760 gene was amplified using ProofStart DNA polymerase (Qiagen) and the primers NCgl2760-left_F (5Ј-GTCACC-CGGGTAAATAAAGGCAACC) and NCgl2760-left_R (5Ј-GATAGGATCCCAATAATGAGGACCG) and cloned into the XmaI/BamHI sites (underlined) of pUC19 (49), creating plasmid pUC-NCgl2760left.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations